2017
DOI: 10.1039/c6cc08844a
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur dioxide prodrugs: triggered release of SO2via a click reaction

Abstract: Sulfur dioxide (SO2) is being recognized as a possible endogenous gasotransmitter with importance on par with that of NO, CO, and H2S. Herein we describe a series of SO2 prodrugs that are activated for SO2 release via a bioorthogonal click reaction. The release rate can be tuned by adjusting the substituents on the prodrug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…[12c] Briefly, compound 1a–b were condensed with a variety of alcohol or amine to afford compounds 2a–i , which were found to exist as a mixture of keto-enol tautomers (Scheme 1). Compounds 2a–i were then reacted with acenaphthylene-1,2-dione, followed by treatment with an acid for dehydration to yield the desired CO prodrugs BW-CO-104-106 , and 108-113 in 20–77% yield.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[12c] Briefly, compound 1a–b were condensed with a variety of alcohol or amine to afford compounds 2a–i , which were found to exist as a mixture of keto-enol tautomers (Scheme 1). Compounds 2a–i were then reacted with acenaphthylene-1,2-dione, followed by treatment with an acid for dehydration to yield the desired CO prodrugs BW-CO-104-106 , and 108-113 in 20–77% yield.…”
Section: Resultsmentioning
confidence: 99%
“…[12c] Cytotoxicity of the other CO prodrugs along with their corresponding products after CO release was studied in Raw 264.7 cells with a drug exposure time of 24 h. The results (Figure S18–19) revealed that most of the compounds tested did not present obvious cytotoxicity at 100 μM, and only a few CO prodrugs ( BW-CO-112, 113, 115, 116, 120 and 121 ) and inactive products ( BW-CP-111/115/120 ) showed cytotoxicity with IC 50 values in the range of 50–100 μM. Clearly, there is no general intrinsic toxicity issues related to this class of compounds, but idiosyncratic toxicity may occur with individual compounds, which can also be addressed by structural optimizations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds were shown to permeate S. aureus , deplete intracellular thiols and induce oxidative stress. While a number of other SO 2 donors were developed, their antibacterial properties are not reported . Together, these SO 2 donors offer unique possibilities for further development if toxicity issues can be sorted out.…”
Section: Introductionmentioning
confidence: 99%